Prosodic realization of Focus in the Albanian language - Jakupi, Qëndresa (East European Journal of Psycholinguistics, 2024)
Prosodic tools have been treated as main elements for focus marking in different languages. Among them, stress is assumed to have a key role in the realization of focus. Researchers such as Selkirk (1995) assume that focus realization occurs when stress interacts with syntactic and phonological components. However, researchers such as Truckenbrodt (1999), Samek-Lodovici (2005; 2006), Féry (2013; 2016), Lee (2013), Yan et al. (2022) disagree with his hypothesis as, according to them, focus is realized through interactions between prosodic structure, syntactic structure, stress, and information structure. According to the latter, this realization of focus can be explained through three constraints: align XP, wrap XP, and stress-focus, which arose from Optimality Theory. Therefore, in order to investigate the prosodic realization of focus in the Albanian language, we will rely on these notions of limitations to see the interactions of different linguistic domains in the realization of informative and emphatic focus through emphasis in our corpus, which consists of: match commentary Albania vs Serbia (2014) and the broadcast Pressing (May 30, 2022). The method used in this work is based on the analysis of the Optimality Theory of sentence stress which integrates insights from the generative linguistics, through which interactions between focus prominence and phrases are highlighted. The results provide evidence that the interactions of these syntactic and prosodic constraints influence the Albanian speaker to realize the focus in different positions within the sentence.